2013
DOI: 10.1037/cpp0000028
|View full text |Cite
|
Sign up to set email alerts
|

Youth Suicide Prevention in Primary Care: A Model Program and Its Impact on Psychiatric Emergency Referrals

Abstract: Primary care is an emerging setting for suicide prevention efforts. Psychologists can play a valuable role in not only consulting to primary care but also assisting with the management of suicidal youth. This article describes the Pennsylvania Youth Suicide Prevention in Primary Care model. After detailing the model, a brief study is reported whereby the intervention of primary care staff training, screening, and available services on referrals to the emergency department (ED) for evaluation and the rate of ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Based on these inclusion criteria, we found four packaged interventions that have been developed and tested for the management of suicide risk in primary care: (a) Wintersteen & Diamond, 2013). A fifth intervention, Improving Mood: Promoting Access to Collaborative Treatment (IMPACT; Unützer et al, 2006), though not developed with the express purpose of managing suicide risk, was also included in this review because it had published outcome data on suicidal behaviors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these inclusion criteria, we found four packaged interventions that have been developed and tested for the management of suicide risk in primary care: (a) Wintersteen & Diamond, 2013). A fifth intervention, Improving Mood: Promoting Access to Collaborative Treatment (IMPACT; Unützer et al, 2006), though not developed with the express purpose of managing suicide risk, was also included in this review because it had published outcome data on suicidal behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…The Pennsylvania YSP-PC program also emphasizes the importance of practitioner education. There is evidence that PCPs are more discerning in the patients they refer to emergency rooms after going through this training (i.e., more likely to utilize other approaches to managing risk in lower risk patients), suggesting the program helps PCPs more accurately screen and refer patients (Wintersteen & Diamond, 2013).…”
Section: Educating Practitionersmentioning
confidence: 99%
“…This study adds to a small body of literature that has examined self‐injury and comorbid suicidal behavior among a sample of adolescents and young adults presenting to primary care (as opposed to emergency rooms, inpatient units, or college samples; Druss & Mauer, ). Primary care has been identified by both the Affordable Care Act and the National Strategy for Suicide Prevention as one of the most important sites for the screening and identification of mental health problems (Wintersteen & Diamond, ; U.S. Department of Health and Human Services, ). Similarly, this is one of the few studies to examine NSSI and STBs among youth in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Although the U.S. Preventative Services Task Force has stated there is insufficient evidence to support universal suicide risk screening in the primary care setting, 11 evidence regarding the efficacy of these programs is rapidly emerging. Studies of universal suicide risk screening programs in emergency room and primary care settings have found that universal suicide risk screening programs can increase suicide risk screening 12,13 and detection 13 rates, decrease acute care utilization, 14 and increase behavioral health linkage rates. 15 In 2017, a landmark study found that universal suicide risk screening paired with a brief intervention in the emergency room decreased subsequent suicide attempts by almost 30%.…”
mentioning
confidence: 99%
“…Additionally, electronic screening has been associated with higher patient satisfaction and completion rates, greater efficiency in documentation and follow-up, and increased linkage to follow-up care. 28 In pediatric samples, electronic screening with a multidisciplinary team approach has been associated with increased linkages to care 14 and decreased acute care referrals. 26 Validated suicide risk screening programs and tools are also beginning to be developed and implemented in medical settings.…”
mentioning
confidence: 99%